An integrated geophysical survey at a landslide-prone area. Issue 1 (1st December 2016) - Suto, Koya; Urosevic, Milovan; Arsenovic, Sinisa; Sugawara, Jun
Abstract : A heavy rainfall of May 2014, caused an extensive disaster to the catchment of River Sava in Serbia and Bosnia and Herzegovina (BiH). The number of landslides exceeded 2000 in Serbia and BiH. This prompted an urgent investigation of the areas which have potential of further landslide. Association of Geoscientists and Environmentalists of Serbia (AGES) initiated a project of geophysical investigation of these areas supported by Geoscientists without Borders (GwB) of Society of Exploration Geophysicists (SEG). Over twenty students participated from three countries and more than ten technical professionals from six countries joined in the project. Reflection seismic, MASW and resistivity surveys were carried out in the Vrazici area in BiH in June 2015. Two survey lines were surveyed totaling about 120 meters along a slope of grassland and orchard. A clear increase of S-wave velocity from 250 to 350m/s at about 3 to 5m below the ground surface is observed by the MASW analysis, which is consistent with the reflection profile at the same area. This depth roughly corresponds to the resistivity boundary at 80 ohm-m. It is interpreted the interface between soft soils and relatively competent rock. The depth profiles of these boundaries show that the soft soils are thicker toward the lower part of the slope. This landslide can be classified as Varnes's classification "earth slide or earth flow".